COGNITIVE DEVELOPMENT: TOWARDS A PLURALISTIC AND COALITIONAL MODEL. - Khabbache, Hicham; Ouazizi, Khalid; Bragazzi, Nicola Luigi; Watfa, Ali Assad; Mrabet, Redouane (Cosmos & History, 2020)
Mainstream classical psychological theories have often favoured a conception of cognitive functioning and development based on uniformity and standardisation. This conception, as we will explain below in more detail, was proven to be fundamentally limited on almost every aspect of it. In contrast, this article adopts a pluralistic and a coalitional conception of cognitive functioning and development. It is pluralistic because we conceive cognitive development to take multiple and variable pathways, and to be operating through various forms of variability: i) intrapersonal, ii) interpersonal, iii) inter-contextual and iv) inter-cultural variability. It is coalitional too in that several processes and factors (indigenous and/or exogenous) combine together to form complementary networks which enable the individual to solve complicated tasks that require high cognitive efforts. This synergistic dynamism ensures the maintenance of networking among the different parts of our cognitive systems. Before addressing the theoretical foundations of the present pluralistic and coalitional approach, it is necessary to rethink some foundational principles of some of the most famous classical theories such as Piaget’s unidirectional theory or “unitary theory”. This review will pave the way for us to unfold the principles of the present approach at hand. We envisage that these principles are the key to the understanding of changes over the development and evolution at different time scales not only in the cognitive and conceptual systems but also in other juxtaposed systems of the humanities. In this regard and as an expansion of this model, we propose, a new line of research, for researchers to carry this model with the aspiration to find the same principles, and may be more, in other fields such as anthropology, sociology, educational sciences and psychopathology. The coherent elements between these disciplines are the cross-board recurrence of some systems (the cognitive, the conceptual, the linguistic ….etc.), cross-board nested time scales, and cross-board emergence of cultural phenomena.